Novel insights into the clinico-radiological spectrum of phenotypes associated to PIGN mutations. (July 2021) - De Giorgis, Valentina; Paoletti, Matteo; Varesio, Costanza; Gana, Simone; Rognone, Elisa; Dallavalle, Gianfranco; Papalia, Grazia; Pichiecchio, Anna
Abstract: Objectives: Autosomic recessive mutations in the PIGN gene have been described in less than 30 subjects to date, in whom multiple congenital anomalies combined with severe developmental delay, hypotonia, epileptic encephalopathy, and cerebellar atrophy have been described as crucial features. A clear-cut neuroradiological characterization of this entity, however, is still lacking. We aim to present three pediatric PIGN mutated cases with an in-depth evaluation of their brain abnormalities. Methods: We present the neuroradiological, clinical, and genetic characterization of three Caucasian pediatric subjects with pathogenic/likely pathogenic variants in the PIGN gene revealed by Next Generation Sequencing analysis. Results: We identified three subjects (two siblings, one unrelated case) presenting with encephalopathy with early-onset epilepsy, hypotonia, and severe global developmental delay. No additional severe multiple congenital anomalies were detected. Neuroradiological evaluation showed extensive quantitative reduction of white matter, severe and progressive cortical atrophy, with frontal predominance and an anteroposterior gradient, combined with cerebellar and brainstem atrophy. Conclusions: Our findings broaden and systematize the neuroradiological spectrum of abnormalities in PIGN related encephalopathy. Furthermore, our dataset confirms that mutations in PIGN gene appear to be pan-ethnic and represent an underestimated cause of early-onset encephalopathy. Highlights: PIGN related syndrome is an underestimated cause of DEE. Multiple congenital anomalies are not constant key feature of the syndrome. MRI findings should be regarded as highly suggestive for PIGN mutation.